Penggunaan Kohesi Gramatikal Pada Wacana Tajuk Rencana Surat Kabar Jawa Pos Edisi Maret 2016 Sebagai Bahan Ajar Bahasa Indonesia Di SMP - Wahyuni, Tri; , Prof. Dr. Abdul Ngalim, M.Hum (2016)
ABSTRACT This study has two objectives (1) Describe the type of grammatical cohesion of discourse editorial in newspaper Jawa Pos edition in March 2016. (2) Describe the grammatical cohesion in discourse editorial Jawa Pos newspaper editions in March 2016 as the Indonesian teaching materials in SMP. This research is a descriptive qualitative research. The object of this research is on the editorial grammatical cohesion Jawa Pos edition in March 2016 as a junior high school teaching materials. The data in this study are words, phrases, and sentences that contain grammatical cohesion. Sources of data in this research is the discourse of the editorial in the newspaper Jawa Pos edition in March 2016. Data collection techniques in this study refer to the method followed by the techniques noted. Data analysis in the research is the method shared with techniques for direct elementd. A technique for the direct element followed by advanced techniques in the form of dressing techniques and techniques vanished. The validity of the data in this study using triangulation theory. The results of this study indicate that. (1) Grammatical cohesion use of contained in the editorial cohesion grammatical markers formed consisting of reference, substitution, ellipsis, and conjunction. (2) Cohesion grammatical discourse editorial Jawa Pos newspaper editions in March 2016 may have been implicated in learning Indonesian in particular junior class VII at KI 4 KD 4.2 with a discussion of the material determines the pronouns, word class, and said transition (conjunction) in the text.